Magnetic petrophysical results from the Hamersley Basin and their implications for interpretation of magnetic surveys - Guo, W.; Li, Zheng-Xiang; Dentith, M. (Taylor & Francis Co Ltd, 2011)
An extensive magnetic petrophysical investigation was carried out in the Hamersley Basin in Western Australia; which hosts large high-grade iron-ore deposits derived from banded iron formations (BIFs). Based on our new results, as well as those from previous studies, we demonstrate that the bulk susceptibility of BIF units has a bimodal distribution caused by the presence of chert-rich and magnetite-rich bands. The mean bulk susceptibility (MBS) of magnetite-rich bands is more than 10 times higher than that of chert-rich bands. Measurements of anisotropy of magnetic susceptibility (AMS) in BIF units show this to vary between 1.06 and 2.76. The natural remanent magnetisation (NRM) carried by iron ores varies with different deposits, and even within individual deposits. NRM measurements on non-ore units defined a northwesterly upward regional magnetic overprint (310°/–27°) present in the Fortescue and Hamersley Groups, and also in the lower Wyloo Group. Modelling of aeromagnetic data over the Hamersley Range demonstrates that the effects of AMS and NRM are significant and must be accounted for. The effects of AMS and NRM on magnetic anomalies due to BIFs depend on the volume fraction of magnetite-rich members in a BIF unit. Forward modelling of magnetic and gravity responses, using petrophysical results summarised in this study, over a mined hematite ore deposit in Tom Price indicates that TMI variations are expected to be significantly reduced in areas of mineralisation. However, magnetic data alone are not a reliable indicator of the presence of mineralisation because of other causes of reduced magnetism in BIFs.